DIMENSI FRAUD TRIANGLE TERHADAP PERILAKU FRAUD PADA JASA TRANSPORTASI BERBASIS ONLINE GOJEK - Djamil, Nasrullah (Universitas Lancang Kuning, 2024)
The objective of this study is to present, test, and analyze the effect of the Fraud Triangle dimensions (pressure, opportunity, and rationalization) on fraud behavior in Go-Jek online transportation services in Pekanbaru City. The study's sample criteria are Gojek driver partners residing in Pekanbaru City, with a particular focus on those employed as Go-Ride drivers. The study sample consisted of 96 respondents. The research method employed was the survey method, whereby primary data were collected from respondents through the distribution of questionnaires directly to Go-Jek driver partners in Pekanbaru City. The data were analyzed using the SPSS application program. The simultaneous test results indicate that pressure, opportunity, and rationalization exert a significant influence on fraud behavior on Gojek online transportation services in Pekanbaru City. The partial test results demonstrate that pressure and opportunity have an effect on fraud behavior on Gojek online transportation services in Pekanbaru City, whereas rationalization has no influence on fraud behavior on these services.